Associations of utilitarian cycling with destinations and street connectivity assessed within multiple buffers - Firas Mohamed; Manoj Chandrabose; Neville Owen; Takemi Sugiyama (Journal of Transport and Land Use)
In examining neighborhood environmental attributes associated with bicycle use, measuring attributes within a buffer area around home has been a common approach. However, buffer sizes have been determined with limited empirical support. This study investigated associations of cycling for utilitarian purposes with destinations and street connectivity measured within empirically informed multiple buffer zones. Household travel survey data collected in Victoria, Australia (2012–20), were used to calculate the mode share of cycling for home-based utilitarian trips in 1,105 Statistical Area Level 1s (SA1s), which contained 43,965 adult participants. Based on the distribution of home-based utilitarian cycling trip distances, three non-overlapping concentric circular buffers were drawn from the centroid of each SA1: 0–1 km (Zone 1); 1–1.8 km (Zone 2); and 1.8–4 km (Zone 3). Two destination density measures (core and expanded destinations) and two intersection density measures (3-way+ and 4-way+ intersections) were assessed within each zone. Two-part regression models examined the associations of environmental measures with the presence of utilitarian cycling (logistic regression) and with the mode share of cycling (linear regression). Logistic regression found that higher destination density in all zones and intersection density in Zone 3 were associated with higher odds of utilitarian cycling trips. Linear regression found that higher destination and intersection densities in Zone 2 were associated with a higher mode share of cycling. Future research could use a buffer area within 1 to 4 km from home to further understand the relationships between the built environment and cycling for utilitarian purposes.